Rhizobia in tropical legumes—XI. survival in the seed environment - Faizah, A.; Broughton, W.J.; John, C. (1980)
Factors affecting rhizobia in the seed environment of the legumes Cajanus cajan, Centrosema pubescens, Glycine max, and Psophocarpus tetragonolobus were investigated. These included the effects of fungicides, insecticides, and herbicides on the survival and growth of rhizobia on agar and in liquid cultures. The pesticides used varied in their toxicity towards rhizobia but many fungicides and insecticides could be used in the vicinity of inoculated seeds. Certain fungicides and insecticides were shown to have little or no effect on the Rhizobium-legume symbiosis of C. cajan, C. pubescens, G. max, and P. tetragonolobus when added directly to inoculated seed. Various protective pelleting procedures were investigated including preparation of coating materials containing rock phosphates from different localities, talc, and bonemeal. These were applied to the seed in mixtures suspended in aqueous solutions of substituted celluloses, or gum arabic. Talc and Christmas Island rock phosphate both proved satisfactory, while “Cellofas” is recommended as the adhesive in this formulation. Soaking seeds before pelleting in an effort to remove anti-rhizobial substances from G. max seeds was beneficial in the case of soyabean cultivar KS437, but harmful when applied to Palmetto seeds.